2021
DOI: 10.33093/ipbss.2021.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workplace Spirituality on Employee Performance

Abstract: Employees in the 21st century seek a work environment which allows them to find a sense of purpose at work, within an atmosphere filled with respect and courteous interactions between the employees and their surroundings. The spiritually-oriented work environment is crucial because it shapes employees’ behaviour at the personal level and eventually, improves employee performance. In this paper, a theoretical framework which explains how the spiritual work environment (inner self, community and meaningful work)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The main implication drawn from these findings is that the sense of purpose obtained from spirituality at the workplace provides employees with internal cues and energy to keep their focus during the demanding and fast-faced working atmosphere (Kendall, 2019). Apart from highlighting instrumental values of work and their contribution, it is also imperative that organizations emphasize the spiritual values of their existence and link the organization's performance to non-financial needs (Latiff, 2021). Benefiel et al (2014) suggested that WPS does not only have personal benefits (joy, satisfaction, and commitment), but has organizational benefits, which is productivity, reduced absenteeism, and turnover.…”
Section: Discussionmentioning
confidence: 96%
“…The main implication drawn from these findings is that the sense of purpose obtained from spirituality at the workplace provides employees with internal cues and energy to keep their focus during the demanding and fast-faced working atmosphere (Kendall, 2019). Apart from highlighting instrumental values of work and their contribution, it is also imperative that organizations emphasize the spiritual values of their existence and link the organization's performance to non-financial needs (Latiff, 2021). Benefiel et al (2014) suggested that WPS does not only have personal benefits (joy, satisfaction, and commitment), but has organizational benefits, which is productivity, reduced absenteeism, and turnover.…”
Section: Discussionmentioning
confidence: 96%